Răspuns :
a)
5 ( 3 x - 2 ) + 3 x - 6 ( 8 x - 13 ) = 16 ( 9 - 2 x ) - 78
15 x - 10 + 3 x - 48 x + 78 = 144 - 32 x - 78
18 x - 48 x + 32 x = 66 - 68
2 x = - 2
x = - 1
_____________________
b)
2 ( 3 x + 4 ) - 5 ( 2 x - 3 ) - 2 = 7 ( 2 x - 4 ) + 2( 8 - 5 x ) + 3 x
6 x + 8 - 10 x + 15 - 2 = 14 x - 28 + 16 - 10 x + 3 x
- 4 x - 7 x = - 12 - 21
- 11 x = - 33
x = ( - 33 ) : ( - 11 )
x = 3
________________
c)
2 ( 3 x - 4 ) + 5 ( 6 x - 7 ) - 3 x = 9 ( x +10 ) + 11 ( x + 12 ) + 8
6 x - 8 + 30 x - 35 - 3 x = 9 x + 90 + 11 x + 132 + 8
33 x - 20 x = 230 + 43
13 x = 273
x = 273 : 13
x = 21
_______________
d)
3 ( 6 x - 5 ) - 2 ( 4 x + 3 ) + 13 = - 2 ( - 4 x + 9 ) + 2 x - 5 ( 3 x - 2 )
18 x - 15 - 8 x - 6 + 13 = 8 x - 18 + 2 x - 15 x + 10
10 x + 5 x = - 8 + 8
15 x = 0
x = 0
a)
5(3x-2)+3x-6(8x-13)=16(9-2x)-78
15x-10+3x-48x+78=144-32x-78
-30x+68=144-32x-78
-30x+68=-32x+66
-30x+68+32x=66
2x+68=66
2x=66-68=-2
x=-1
b)
2(3x+4)-5(2x-3)-2=7(2x-4)+2(8-5x)+3x
6x+8-10x+15-2=14x-28+16-10x+3x
-4x+21=14x-28+16-10x+3x
-4x+21=7x-12
21=7x-12+4x
21=11x-12
21+12=11x
33=11x
[tex] \frac{33}{11} = x[/tex]
x=3
c)
2(3x-4)+5(6x-7)-3x=9(x+10)+11(x+12)+8
6x-8+30x-35-3x=9x+90+11x+132+8
33x-43=9x+90+11x+132+8
33x-43=20x+230
33x=20x+230+43
33x=20x+273
33x-20x=273
13x=273
[tex]x = \frac{273}{13} = 21 [/tex]
d)
3(6x-5)-2(4x+3)+13=-2(-4x+9)+2x-5(3x-2)
18x-15-8x+6+13=8x-18+2x-15x+10
10x-8=8x-18+2x-15x+10
10x-8=-5x-8
10x=-5x
-2x=x
0=x+2x
0=3x
x=0
5(3x-2)+3x-6(8x-13)=16(9-2x)-78
15x-10+3x-48x+78=144-32x-78
-30x+68=144-32x-78
-30x+68=-32x+66
-30x+68+32x=66
2x+68=66
2x=66-68=-2
x=-1
b)
2(3x+4)-5(2x-3)-2=7(2x-4)+2(8-5x)+3x
6x+8-10x+15-2=14x-28+16-10x+3x
-4x+21=14x-28+16-10x+3x
-4x+21=7x-12
21=7x-12+4x
21=11x-12
21+12=11x
33=11x
[tex] \frac{33}{11} = x[/tex]
x=3
c)
2(3x-4)+5(6x-7)-3x=9(x+10)+11(x+12)+8
6x-8+30x-35-3x=9x+90+11x+132+8
33x-43=9x+90+11x+132+8
33x-43=20x+230
33x=20x+230+43
33x=20x+273
33x-20x=273
13x=273
[tex]x = \frac{273}{13} = 21 [/tex]
d)
3(6x-5)-2(4x+3)+13=-2(-4x+9)+2x-5(3x-2)
18x-15-8x+6+13=8x-18+2x-15x+10
10x-8=8x-18+2x-15x+10
10x-8=-5x-8
10x=-5x
-2x=x
0=x+2x
0=3x
x=0